Impact of manual therapy on body posture-3-D analysis with rasterstereography – pilotstudy - Alessia Celine Harhoff; Tobias Pohl; Christine Loibl; Werner Adler; Martin Süßenbach-Mädl; Johannes Ries; Anna Seidel; Manfred Wichmann; Ragai-Edward Matta (Head & Face Medicine, 2024)
Abstract Introduction The relationship between posture and temporomandibular disease (TMD) is unclear. The aim of our study was to determine the influence of manual therapy (MT) on posture in TMD patients compared with healthy subjects. Material/method After consideration of inclusion and exclusion criteria, 30 subjects were included. These were divided into two groups: group A comprised 15 healthy subjects and group B 15 patients with present proven TMD disease. Rasterstereographic images were taken at different times. Group A subjects were scanned twice within half a year and group B before initiation as well as after the first MT and after completion of the prescribed MT. The different posture variables were calculated using DIERS Formetric software. Results To illustrate the differences between the two groups, 10 different postural variables were examined. Significant differences between the two groups were observed in pelvic tilt, surface rotation, and kyphotic apex. Pelvic tilt: mean = 7.581, p-value = 0.029; surface rotation: mean = 3.098, p = 0.049; and mean kyphotic apex = 11.538 and 11.946, respectively, with p-values of 0.037 and 0.029, respectively. Conclusion MT leads to a change in posture in TMD patients. This could influence the course of TMD treatment.